The role of SEM and infrared spectroscopy techniques in identification of the mineralogy of kidney stones: case study from Fallujah City, Western Iraq - Hassan A.A. Al-Jumaily; Omar A.M. Mohammad; Anwaar S.J. Al-Maadhidi (Tikrit Journal of Pure Science)
The current study is concerned with the mineralogical aspects of kidney stones from urolithiasis patients of different ages and genders in Fallujah city hospital. The following techniques were implemented as follows; X - ray diffraction (XRD) used to recognize the mineral components of the studied kidney stones, Infrared Spectroscopy (IR) to discover the type of chemical compounds of the studied kidney stones, Scanning Electron Microscopy (SEM) with Energy Dispersive X-Ray Analysis (EDX) to determine the mineralogy and the various chemical components in the kidney stones. The results show that the kidney stones are composed of five mineral groups and these are; mixed stone group, calcium oxalate, phosphate stone, uric acid, and cholesten. The cholesten has been diagnosed for the first time in Iraq, which might be linked to the diet type that includes high levels of cholesterol. Furthermore, the most common mineral group in the study area is the mixed stone which occurs in males more than females for the ages of 40 to 50 years old